The Potential of Web-Based Historical Sources as Learning Resources to Foster Students’ Historical Thinking Skills - Widiadi, Aditya Nugroho; Sheehan, Mark; Shep, Sydney (Paramita: Historical Studies Journal, 2022)
To foster students’ historical thinking in Indonesia, teachers should not merely use textbooks as the only learning resource. They must utilize primary sources in teaching history that are important to encourage students to think historically. Unfortunately, it was not easy to access primary sources in Indonesia. For that reason, this study explored alternative learning resources to overcome the main difficulty faced by history teachers in Indonesia in fostering students’ historical thinking skills. This study aimed to develop web-based historical sources as learning resources and evaluate its potential to foster students’ historical thinking skills in Indonesia. As evaluation research, this study applied educational research and development approach. The results of this study indicated that the website that had been developed had challenges and opportunities in fostering students’ historical thinking skills in Indonesia.Untuk menumbuhkan keterampilan berpikir sejarah siswa di Indonesia, guru sejarah seharusnya tidak hanya mengandalkan buku teks sebagai satu-satunya sumber belajar. Mereka juga harus memanfaatkan sumber-sumber primer dalam pembelajaran sejarah yang begitu penting dalam mendorong siswa berpikir secara historis. Sayangnya, tidak mudah untuk mengakses sumber primer di Indonesia. Oleh karena itu, penelitian ini mengeksplorasi sumber belajar alternatif untuk mengatasi kesulitan utama yang dihadapi oleh guru sejarah di Indonesia dalam menumbuhkan keterampilan berpikir sejarah siswa. Penelitian ini bertujuan untuk mengembangkan sumber belajar sejarah berupa website yang berisi sumber-sumber sejarah dan sekaligus mengevaluasi potensinya dalam menumbuhkan keterampilan berpikir sejarah siswa di Indonesia. Sebagai kajian evaluasi, penelitian ini menggunakan pendekatan penelitian dan pengembangan. Hasil penelitian ini menunjukkan bahwa website yang telah dikembangkan memiliki beberapa tantangan sekaligus kesempatan baik dalam menumbuhkan keterampilan berpikir sejarah siswa di Indonesia.Cite this article: Widiadi, A.N., Sheehan, M., Shep, S. (2022). The Potential of Web-Based Historical Sources as Learning Resources to Foster Students’ Historical Thinking Skills. Paramita: Historical Studies Journal, 32(1), 138-148. http://dx.doi.org/10.15294/paramita.v32i1.31048